Optimization, and in vitro and in vivo evaluation of etomidate intravenous lipid emulsion - Dandan Geng; Yan Li; Chunyan Wang; Bo Ren; Heping Wang; Chensi Wu; Yirong Zhang; Linlin Zhao; Ligang Zhao (Taylor & Francis Group, 2021)
The aim of this investigation was to develop an etomidate intravenous lipid emulsion (ETM-ILE) and evaluate its properties in vitro and in vivo. Etomidate (ETM) is a hydrophobic drug, and organic solvents must be added to an etomidate injectable solution (ETM-SOL) to aid dissolution, that causes various adverse reactions on injection. Lipid emulsions are a novel drug formulation that can improve drug loading and reduce adverse reactions. ETM-ILE was prepared using high-pressure homogenization. Univariate experiments were performed to select key conditions and variables. The proportion of oil, egg lecithin, and poloxamer 188 (F68) served as variables for the optimization of the ETM-ILE formulation by central composite design response surface methodology. The optimized formulation had the following characteristics: particle size, 168.0 ± 0.3 nm; polydispersity index, 0.108 ± 0.028; zeta potential, −36.4 ± 0.2 mV; drug loading, 2.00 ± 0.01 mg/mL; encapsulation efficiency, 97.65% ± 0.16%; osmotic pressure, 292 ± 2 mOsmol/kg and pH value, 7.63 ± 0.07. Transmission electron microscopy images showed that the particles were spherical or spheroidal, with a diameter of approximately 200 nm. The stability study suggested that ETM-ILE could store at 4 ± 2 °C or 25 ± 2 °C for 12 months. Safety tests showed that ETM-ILE did not cause hemolysis or serious vascular irritation. The results of the pharmacokinetic study found that ETM-ILE was bioequivalent to ETM-SOL. However, a higher concentration of ETM was attained in the liver, spleen, and lungs after administration of ETM-ILE than after administration of ETM-SOL. This study found that ETM-ILE had great potential for clinical applications.